2021
DOI: 10.1016/j.phrs.2021.105820
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural compounds as SARS-CoV-2 entry inhibitors by molecular docking-based virtual screening with bio-layer interferometry

Abstract: Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which enter the host cells through the interaction between its receptor binding domain (RBD) of spike glycoprotein with angiotensin-converting enzyme 2 (ACE2) receptor on the plasma membrane of host cell. Neutralizing antibodies and peptide binders of RBD can block viral infection, however, the concern of accessibility and affordability of viral infection inhibitors has been raised. Here, we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 38 publications
0
52
0
1
Order By: Relevance
“…Bio-layer interferometry allows the calculation of the association rate (k on ), dissociation rate (k dis ) and dissociation constant (K D ). This technique has been adopted to screen RBD ligands [17,48] in combination with virtual screening [49,50]. The results of the bio-layer experiments are presented in Table 1.…”
Section: Bio-layer Interferometrymentioning
confidence: 99%
“…Bio-layer interferometry allows the calculation of the association rate (k on ), dissociation rate (k dis ) and dissociation constant (K D ). This technique has been adopted to screen RBD ligands [17,48] in combination with virtual screening [49,50]. The results of the bio-layer experiments are presented in Table 1.…”
Section: Bio-layer Interferometrymentioning
confidence: 99%
“…On a literature survey, it was found that vasicine has shown activity against Influenza Virus Infection (Chavan et al 2013 ). Iso-chlorogenic acid has a potent anti-hepatitis B activity (Hao et al 2012 ), and antienterovirus (Cao et al 2017 ), one of its derivate iso-chlorogenic acid A has been proven by the in vitro study to inhibit viral entry into the cell at 100 micromolar concentration (Zhang et al 2021 ). Catechin inhibits both Mpro and spike protein of SARS-CoV-2 predicted by using computational study (Srivastava et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…When infected with COVID-19, SARS-CoV-2 first binds to ACE2 present in the cell membrane, enters the cell, and abnormally changes the ACE2 signaling transduction, resulting in acute myocarditis and lung damage [ 18 ]. That is, normally ACE2 were expressed in the cell membranes of the heart and lungs, and receptor binding domain (RBD) of the SARS-CoV-2 spike glycoprotein binds to each other with ACE2 and enters the heart and lung tissue cells through interaction, thereby inhibiting the function of the ACE2 can block SARS-CoV-2 virus infection [ 19 ] ( Fig. 3 ).…”
Section: Panax Ginseng and Ginsenosides Against Cardiac Pathogenesis Of Covid-19mentioning
confidence: 99%
“…In line with the above observations, 20(S)-ginsenoside Rg3, the main active ingredient of panax ginseng, blocks RBD-ACE2 interaction through direct inhibition of RBD of the SARS-CoV-2 spike glycoprotein. That is, RBDof SARS-CoV-2 spike glycoproteins to cell membranes in the heart and lung tissue were blocked by 20(S)-ginsenoside Rg3 and 20(R)-ginsenoside Rg3 [ 19 ]. In addition, recent studies have shown that 20(S)-ginsenoside Rg3 and 20(R)-ginsenoside Rg3 effectively inhibited viral infection of SARS-CoV-2-like lentivirus and SARS-CoV-2 virus in cells expressing receptors of human SARS-CoV-2 spike glycoprotein.…”
Section: Panax Ginseng and Ginsenosides Against Cardiac Pathogenesis Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation